1992
DOI: 10.1111/j.1651-2227.1992.tb12227.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor in human and bovine milk

Abstract: The concentration of epidermal growth factor in human and bovine milk was measured by radioreceptor assay. Both human placental plasma membranes and a human epidermoid carcinoma cell were used as the epidermal growth factor receptor source in the assay. The use of placental plasma membrane in the radioreceptor assay gave erroneous results for bovine milk and overestimated the concentration of epidermal growth factor in human milk. Intact cells appear to provide a more accurate measure of the concentration of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 19 publications
(4 reference statements)
3
28
0
2
Order By: Relevance
“…Pakkanen and Aalto (1997) reported that the concentrations of IGF-I and IGF-II in colostrum range from 50 to 2000 μg.L −1 and 200-600 μg.L −1 , respectively, whereas mature milk contains <10 μg.L −1 of each. Yagi et al (1986) found that the concentration of EGF in colostrum and milk was 324 and 155 μg.L −1 , respectively; however, Iacopetta et al (1992) reported the concentration of EGF in colostrum and milk to be 4-8 and <2 μg.L −1 , respectively. It should be noted that reported levels of growth factors vary significantly depending on the method of quantitation used.…”
Section: Growth Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pakkanen and Aalto (1997) reported that the concentrations of IGF-I and IGF-II in colostrum range from 50 to 2000 μg.L −1 and 200-600 μg.L −1 , respectively, whereas mature milk contains <10 μg.L −1 of each. Yagi et al (1986) found that the concentration of EGF in colostrum and milk was 324 and 155 μg.L −1 , respectively; however, Iacopetta et al (1992) reported the concentration of EGF in colostrum and milk to be 4-8 and <2 μg.L −1 , respectively. It should be noted that reported levels of growth factors vary significantly depending on the method of quantitation used.…”
Section: Growth Factorsmentioning
confidence: 99%
“…The main growth factors in colostrum and milk are epidermal growth factor (EGF) (Yagi et al 1986;Iacopetta et al 1992), betacellulin (BTC) (Bastian et al 2001), insulin-like growth factor I (IGF-I) (Collier et al 1991), IGF-II (Schams 1994), transforming growth factor-β1 (TGF-β1) (Ginjala and Pakkanen 1998), TGF-β2 (Cox and Burk 1991), fibroblast growth factor 1 and 2 (FGF1 and FGF2) and platelet-derived growth factor (PGDF) (Belford et al 1997).…”
Section: Growth Factorsmentioning
confidence: 99%
“…Amniotic fluid contains significant concentrations of EGF that gradually increase during pregnancy, with the highest level achieved at the end of the normal gestation period (36). In contrast to human milk, EGF is absent in commercially available infant formulas (37,38). Clinical studies have shown reduced serum and salivary EGF levels in neonates with NEC when compared with healthy babies (39,40).…”
mentioning
confidence: 99%
“…In human milk, EGF has been identified as a major growthpromoting factor [38], whereas there seems to be very little, if any, EGF in bovine milk [29]. Instead, the major growthpromoting factors identified in bovine milk seem to be PDGF [27] and IGF-I and IGF-II [28].…”
Section: Discussionmentioning
confidence: 99%
“…In bovine milk and colostrum, cell growth stimulatory activity has been attributed to a number of peptide growth factors including platelet-derived growth factor (PDGF) [27] and insulin-like growth factor I and II (IGF-I and IGF-II) [28]. EGF, although abundant in human milk, has not been unequivocally detected in bovine milk or colostrum [29].…”
Section: Introductionmentioning
confidence: 99%